Engagement Strategies in Electronic Tools English Online Learning: Higher Education Context - Rizky Eka Prasetya (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTThe study aimed to explore and investigate the versatility, capacity, and adaptability for accommodating online English learning. The qualitative approach was employed in the study with a descriptive research design. 86 participants responded to the survey, and 25 semi-structured interviews were adjusted from the National Survey of Student Engagement (NSSE). The study’s findings have implications for employing online instructors, instructional designers, and administrators to increase online course engagement. The study exposed four recommendations based on the finding, including instructional elements of collaborated and interactive activities, integrated electronic tests applied on mobile phones, and Enhanced Social familiarity. English lecturers preferred to use Moodle and Google classroom as their daily Learning Management System (LMS) in the study context. The interactive tools intended to apply with QuizGame and Wirewax while conference communication instrument approved to the Google Meeting and Skype. Conclusively, the study offered implications for practice by confirming and presenting the online tools approach that might be utilized to engage and implement online English learning education in Higher Education circumstances.ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi dan menyelidiki keserbagunaan, kapasitas, dan kemampuan beradaptasi untuk mengakomodasi pembelajaran daring bahasa Inggris. Pendekatan kualitatif digunakan dalam penelitian ini dengan desain penelitian deskriptif. 86 peserta menanggapi survei, dan 25 wawancara semi-terstruktur disesuaikan dari National Survey of Student Engagement (NSSE). Temuan penelitian ini memiliki implikasi untuk mengenlola instruktur daring, perancang instruksional pembelajaran, dan administrator untuk meningkatkan keterlibatan kelas daring. Studi ini memaparkan empat rekomendasi, termasuk elemen instruksional dari aktivitas kolaborasi dan interaktif, tes elektronik terintegrasi yang diterapkan pada ponsel, dan Peningkatan kedekatan Sosial. Instruktur atau dosen bahasa Inggris lebih menggunakan Moodle dan Google classroom sebagai Learning Management System (LMS) harian mereka dalam konteks belajar daring. Keterlibatan alat interaktif dimaksudkan untuk penerapan dengan QuizGame dan Wirewax sementara instrumen komunikasi konferensi digunakan dalam Google Meeting dan Skype. Secara meyakinkan, penelitian ini menawarkan implikasi untuk praktik dengan mengonfirmasi dan menyajikan pendekatan alat daring sehingga dapat digunakan untuk melibatkan dan mengimplementasikan pendidikan pembelajaran bahasa Inggris daring di lingkungan Pendidikan Tinggi.